System of equations for antenna array beam pattern nulling - Erokhin, A. A.; Salomatov, Yu. P.; Panko, V. S.; Sugak, M. I. (Proceedings (IEEE International Siberian Conference on Control and Communications. Online), 2016)
The synthesis method of a beam pattern with nulls in specified directions is presented. A solution of the system of equations is used in the synthesis of the beam pattern. The expression for calculating of the beamformer complex weights is derived.